From a taller tower : the rise of the American mass shooter - McGraw, Seamus (University of Texas Press, 2021)
"This book is a deep dive into mass shootings--events in which one or more gunmen shoot more than four people--which have become increasingly common, particularly in America, over the last six decades. The book opens on a personal note, describing an event in which the author failed to protect an innocent man from violence, which he likens to our national inability to act and protect each other from these atrocities. From there, he goes back to August 1, 1966, when Charles Whitman murdered more than a dozen people with a sniper's rifle from atop the University of Texas tower. McGraw posits Whitman as the first mass shooter of the era, and uses his case to begin exploring the myths, tropes, and truths of this phenomenon"--